Self-Regulatory Depletion Enhances Neural Responses to Rewards and Impairs Top-Down Control - Wagner, Dylan D.; Altman, Myra; Boswell, Rebecca G.; Kelley, William M.; Heatherton, Todd F. (Psychological Science, 2013)
To be successful at self-regulation, individuals must be able to resist impulses and desires. The strength model of self-regulation suggests that when self-regulatory capacity is depleted, self-control deficits result from a failure to engage top-down control mechanisms. Using functional neuroimaging, we examined changes in brain activity in response to viewing desirable foods among 31 chronic dieters, half of whom completed a task known to result in self-regulatory depletion. Compared with nondepleted dieters, depleted dieters exhibited greater food-cue-related activity in the orbitofrontal cortex, a brain area associated with coding the reward value and liking aspects of desirable foods; they also showed decreased functional connectivity between this area and the inferior frontal gyrus, a region commonly implicated in self-control. These findings suggest that self-regulatory depletion provokes self-control failure by reducing connectivity between brain regions that are involved in cognitive control and those that represent rewards, thereby decreasing the capacity to resist temptations.